The Phenomenon Of On-Street Parking In A Residential Ares In Batam City - Yusra Aulia Sari (Universitas Mercu Buana, 2021)
This research examines residential parking use in one Indonesian city, Batam via SNI 03-1733-2004 concerning road groupings in residential neighborhoods (secondary local road I, secondary local road II, secondary local road III). This is a digest of the paper describing in brief the background, problems, methods, findings, and conclusion. The results of this research found that on average it was filled with four-wheeled vehicles parked because there were 86,9% of the width of the road in the respondents residential area allowing for parking. Around 59,3% of respondents have private parking lots but 19,8% of respondents use their private parking lots as another function. Based on the comfort of the road in a residential area, there were 56,1% of respondents felt comfortable and 77% of the neighbouring respondents were not disturbed by vehicles that were parked outside private land. With 60,2% of the respondents four-wheeled vehicles parked along a residential neighborhood road, there was a 24% commotion. The decrease in road space capacity caused by four-wheeled vehicles parked was 19,35% on secondary local roads I, 20% on secondary local roads II and 37,5% on secondary local roads III. Parking policies on residential neighborhood roads are not listed in Batam city regulations.